Life-cycle assessment and life-cycle costs: a framework with case study implementation focusing on residential heating systems - Glick, Scott, author; Gloeckner, Gene, advisor; Guggemos, Angela A., advisor (Colorado State University. Libraries, 2007)
In 2004 the U.S. residential housing industry accounted for an estimated 21% of total carbon dioxide emissions for an average of 11.3 metric tons of carbon dioxide per single family home. One of the main contributors to these emissions is the residential heating system. Traditionally heating systems are chosen by owners and designers based on first costs. This does not provide a complete picture of total costs. To better understand the total costs of owning and using a building, life-cycle cost methodology can be used to identify, monitor, and decrease energy cost over a buildings' life-cycle. However this methodology does not consider the environmental consequences of system choice. Life-cycle assessment can increase the understanding of the environmental consequences attributable to a specific product, process, or system choice. This research uses both methodologies in the decision making process relating to heating system choice and design. This research created frameworks for performing life-cycle environmental and economic assessment using existing free online tools. Both frameworks were used in a comparative case study of two residential heating systems, gas forced air and radiant solar, for inclusion in a home in Fort Collins, Colorado, U.S.A. The proposed home consists of 3000 square feet, has excellent solar access, has 2x6 walls with superior insulation, is located at an elevation of 5000-6000 feet, and is in a four season climate. The results of an analysis of the life-cycle cost and life-cycle assessment data initially indicated the gas forced air system was the better choice both environmentally and economically. The data were then used to pinpoint solar radiant system components for replacement trying to reduce both costs and environmental impacts. This analysis indicated the replacement of the solar collectors with a gas fired boiler in the solar radiant system improved both system costs and environmental impacts. The new system had similar environmental impacts to the gas forced air system, and fewer environmental impacts than the solar radiant system. This substitution had less impact on the life-cycle cost making the modified system still cost-prohibitive when compared to the gas forced air system.
Keywords: green buildings; life cycle assessment; life cycle costs; residential heating; civil engineering